Changes in soil moisture and riparian forest structure after a dam construction - Vale, Vagner Santiago do; Júnior, Jamir Afonso do Prado; Lopes, Sérgio de Faria; Arantes, Carolina de Silvério; Nascimento, Diego Raymundo; Neto, Olavo Custódio Dias; Gusson, André Eduardo; Santos, Lilian Cristina da Silva; Schiavini, Ivan (Iheringia, Série Botânica., 2019)
This study evaluated the impacts of water flow reduction in soil moisture and changes in the arboreal community in a riparian forest in Minas Gerais. Our hypothesis is that few years after river flow reduction can alter soil moisture and change tree community structure. We performed soil moisture analyses to confirm reduction in soil moisture and a four-year-monitoring of the tree community structure in 1.1 ha of riparian forest. Soil moisture was reduced, especially during the dry season at the sector located near the original river flow. In this sector we found higher mortality and broken stems of living trees, strongly reducing basal area and causing a little reduction in trees density. This study highlights the strong impacts of dams’ construction in the flora and water availability downstream from the dam.